(untitled) (Revista de Medicina Clinica, 2023)
Clinical snapshot on "Biamniotic Monochorionic Twin Gestation, TRAP Sequence. Fetal Anemia and Acardiotic Fetus" presented in volume 7 number 3 of 2023 of Revista de Medicina Clínica